Pemikiran Hukum Tata Negara Islam - Budisetyowati, Dwi Andayani; Rohman, Adi Nur; Zainab, Nina (Jimly School of Law and Government, 2024)
An Islamic state is a state that bases its constitution on the teachings of the Qur'an, where the state aims to achieve the people's welfare. In order to achieve this goal, Islam recognizes political thought as a means to realize this goal. One form of political thought is exemplified by the change of head of state in Medina after the death of the Prophet Muhammad, SAW. Islamic politics not only focuses on the change of head of state but also upholds the application of the values ​​of the Qur'an as the foundation for the formation of the state structure and the basis for managing the state. Although similar, the view of Islamic ideology as the basis for the state still causes debate to this day because there are Islamic views that are not in line with the foundation of the modern state. This conceptual paper discusses two main topics: the first concept of the state in the Qur'an and the second relationship between Islam and the state. The results of the author's study show that, first, the Qur'an does not explicitly regulate the form of the state but explains the principles and procedures for the state, such as governance, equality and protection of rights, politics, economics, and trade. Second, there is a correlation between religious ideology and the context of the state where religion is used as the basis for instilling values ​​in the state. However, this idea has been debated and developed depending on the paradigm used. There are at least three schools of theory in the relationship between Islam and the state, including conservative, modernist, and secular.